2017
DOI: 10.1007/s00464-017-5426-z
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve takes 65 repetitions of totally extraperitoneal laparoscopy on inguinal hernias for reduction of operating time and complications

Abstract: After an initial reduction, the mean operating time stabilised after 65 cases. A reduction in the rate of complications was observed after 35 cases, and a rate of 97% of early discharge was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 24 publications
2
44
0
Order By: Relevance
“…In addition, surgeons performing SILS must have specific skills, such as the ability to manipulate the laparoscopic instruments in a confined operating space, and they must overcome difficulties related to the in‐line positioning of the laparoscope and the close proximity of the working instruments with limited triangulation and motion. Previous reports suggested that 30–80 cases were needed to master the learning curve for TEP . In the present study, the operating time decreased gradually after 20 cases and stabilized at about 60 min after 40 cases; the rate of peritoneal injury also tended to decrease in the experienced period.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, surgeons performing SILS must have specific skills, such as the ability to manipulate the laparoscopic instruments in a confined operating space, and they must overcome difficulties related to the in‐line positioning of the laparoscope and the close proximity of the working instruments with limited triangulation and motion. Previous reports suggested that 30–80 cases were needed to master the learning curve for TEP . In the present study, the operating time decreased gradually after 20 cases and stabilized at about 60 min after 40 cases; the rate of peritoneal injury also tended to decrease in the experienced period.…”
Section: Discussionsupporting
confidence: 59%
“…Surgeons performing SILS‐TEP have to overcome the many difficulties associated with a confined operating space, including in‐line positioning of the laparoscope, close proximity of the working instruments with limited triangulation, and the limited range of motion of the laparoscope and instruments. Although a previous report suggested that 30–80 cases were needed to master the learning curve for TEP , there have been no reports on the learning curve for SILS‐TEP. The purpose of this study was to clarify the learning curve for SILS‐TEP using moving averages.…”
Section: Introductionmentioning
confidence: 99%
“…[51] The Cooperian philosophy is still timely and rather more true in the current laparoscopic era for safe and successful outcome as emphasized recently by Annibali et al and Bhatia, [52,53] and it demands crisp precise flawless anatomical knowledge, [16,26,53] long strenuous laparoscopic learning, [16,21] and significant laparoscopic experience of >30-80 cases, [27,[55][56][57][58][59] for the seamless surgery, and that it also poses new Section: Surgery dangers of modern technological approaches, warranting more anatomic research. [28,33] Anecdotal experiences published in the literature indicate that the fascial arrangements and relationships of structures near the deep inguinal ring are unfamiliar from the laparoscopic perspectives and are not generally known to most of the laparoscopic hernia surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15,27] In addition to the need of the sound technical learning and handson training, it is mandatory to acquire precise anatomical knowledge before performing the technically demanding TEPP hernioplasty. [21,27,55,59,[63][64][65] In addition to the technical dexterity, there are some drawbacks for the common adoption of this technique including increased operative times, complications during the early learning curve, and almost absolute necessity for general anaesthesia. [14,15] The easily fissile plane of the preperitoneal surgical dissection was found avascular as long as both fascia & fat was visible on either side of the dissection plane -anteriorly the diaphanous transversalis fascia and posteriorly the preperitoneal fascia covering the preperitoneal fat, suggesting separate embryonic origin of the transversalis fascia (outermost layer) and preperitoneal fascia (intermediate layer), as also documented by Mark Hayes in terms of the outermost layer (transversalis fascia), [66] the intermediate layer (preperitoneal or extraperitoneal fascia) and the innermost layer (peritoneum).…”
Section: Discussionmentioning
confidence: 99%
“…Tension-free repairs are the current methods of choice in groin hernia surgery because they have a more comfortable postoperative course and lower recurrence rates. Tension-free repairs using synthetic material via video-endoscopic interventions are widely accepted in hernia surgery [1]. Transabdominal preperitoneal (TAPP) and total extraperitoneal (TEP) methods with a posterior approach have been implemented as video-endoscopic techniques.…”
Section: Introductionmentioning
confidence: 99%